A Review on the Potential of UiO-66-NH₂ Metal-Organic Framework as a Proton Exchange Membrane in Microbial Fuel Cells - Dewi, Syahrani Riana; Beladona, Siti Unvaresi Misonia; Toepak, Erwin Prasetya; Iqbal, Rendy Muhammad (Universitas Islam Indonesia, 2026)
The escalating global demand for energy has accelerated the development of efficient and environmentally sustainable renewable energy technologies. Among these, Microbial Fuel Cells (MFCs) have emerged as a promising bioelectrochemical system capable of converting chemical energy derived from organic substrates into electrical energy through microbial metabolism. A critical component influencing MFC performance is the Proton Exchange Membrane (PEM), which facilitates the selective transport of H⁺ ions from the anode to the cathode while preventing substrate crossover. Conventional PEM materials, such as Nafion, exhibit several limitations, including high cost and suboptimal performance under specific operational conditions. Consequently, recent research has increasingly focused on the development of Mixed Matrix Membranes (MMMs) that integrate polymer matrices with inorganic fillers, particularly Metal–Organic Frameworks (MOFs), to enhance membrane properties. Among various MOFs, UiO-66-NH₂ has attracted considerable attention due to its exceptional chemical and thermal stability, as well as the presence of amine (-NH₂) functional groups that improve hydrophilicity and facilitate proton transport pathways. This review evaluates the potential application of UiO-66-NH₂ as a functional filler in polyvinylidene fluoride (PVDF)-based membranes to enhance PEM performance in MFC systems. Evidence from recent studies indicates that incorporating UiO-66-NH₂ into PVDF matrices can significantly improve proton conductivity while maintaining adequate mechanical strength, positioning this composite membrane as a promising and sustainable alternative for advanced bioelectrochemical energy technologies.